Ruptured splenic artery aneurysm in the course of acute pancreatitis - Laca, Emilio; Segura, Juan (Cirugía del Uruguay, 1979)
Report of a case of grave intraperitoneal hemorrhage (subcapsular splenic hematoma) which appeared on the 6th day of post - operatory of acute necrotic biliary transit pancreatitis, due to rupture oI an aneurysm of the juxtahilar segment of splenic artery. The author puts forth the hypothesis that sorne of the pancreatic patients who die in hypovolemic shock, might be treated satisfactorily provided the possibility of hemorrhage being due to erosion o'r rupture of a thick arterial or venous vessel', be considered. It is deemed ikely that formation of this type of aneurysm be acute and secondary to the action of pancreatic enzymes on previously undamaged arterial paries.